Inhibition of PI3K by PX-866 Prevents Transforming Growth Factor-α–Induced Pulmonary Fibrosis - Le Cras, Timothy D. (American Society for Investigative Pathology, 2010)
Transforming growth factor-α (TGFα) is a ligand for the epidermal growth factor receptor (EGFR). EGFR activation is associated with fibroproliferative processes in human lung disease and animal models of pulmonary fibrosis. EGFR signaling activates several intracellular signaling pathways including phosphatidylinositol 3′-kinase (PI3K). We previously showed that induction of lung-specific TGFα expression in transgenic mice caused progressive pulmonary fibrosis over a 4-week period. The increase in levels of phosphorylated Akt, detected after 1 day of doxycycline-induced TGFα expression, was blocked by treatment with the PI3K inhibitor, PX-866. Daily administration of PX-866 during TGFα induction prevented increases in lung collagen and airway resistance as well as decreases in lung compliance. Treatment of mice with oral PX-866 4 weeks after the induction of TGFα prevented additional weight loss and further increases in total collagen, and attenuated changes in pulmonary mechanics. These data show that PI3K is activated in TGFα/EGFR-mediated pulmonary fibrosis and support further studies to determine the role of PI3K activation in human lung fibrotic disease, which could be amenable to targeted therapy.